Computer-Aided Process Design of the Separation of a Two-Component Steroid Mixture by Simulated Moving Bed Technique I. - Temesvári, Krisztina; Aranyi, Antal; Balogh, Sándor; Bánkuti, Gyöngyi; Csukás, Béla (Acta Agraria Kaposváriensis, 2004)
A method, combining laboratory scale equilibrium and elution experiments, simplified model based heuristic rules, as well as sophisticated dynamic simulation was applied to design the separation of a two-component steroid crude mixture in a given laboratoryscale Simulated Moving Bed unit. The adsorption equilibrium isotherms of the pure components were determined by Frontal Analysis method. Langmuir isotherm model was fitted to the measured isotherm data. With the knowledge of these a priori data, elution chromatograms of the pure components were measured for the identification of the hydrodynamic and kinetic parameters in the SMB columns. The first estimations of the SMB parameters were derived by means of Morbidelli’s triangle theory. Starting from a feasible solution, stepwise improvement of the SMB process was carried out by the detailed dynamic simulation, according to a strategy, based on the role of the design parameters. Simultaneously, laboratory-scale SMB experiments were carried out. Agreement between the measured and calculated data was found. In the next step, the dynamic simulation was applied for the improvement of the specific capacity parameters of the SMB separation (production rate, solvent consumption, recovery). In comparison with the simple elution chromatographic separation method, considerable improvement of specific capacity parameters was obtained.